The Role of the Transcription Factor Nuclear Factor-kappa B in Thyroid Autoimmunity and Cancer - Giuliani, Cesidio; Bucci, Ines; Napolitano, Giorgio (Frontiers in Endocrinology, 2018)
Nuclear factor-kappa B (NF-kB) is a ubiquitous transcription factor that is involved in inflammatory and immune responses, and also in regulation of expression of many other genes related to cell survival, proliferation, and differentiation. In mammals, NF-kB comprises five subunits that can bind to promoter regions of target genes as homodimers or heterodimers. The most common dimer is the p50/p65 heterodimer. The several combinations of dimers that can be formed contribute to the heterogeneous regulation of NF-kB target genes, and this heterogeneity is further increased by interactions of the NF-kB dimers with other transcription factors, such as steroid hormone receptors, AP-1, and CREB binding proteins. In the thyroid, several studies have demonstrated the involvement of NF-kB in thyroid autoimmunity, thyroid cancer, and thyroid-specific gene regulation. The role of NF-kB in thyroid autoimmunity was hypothesized more than 20 years ago, after the finding that the binding of distinct NF-kB heterodimers to the major histocompatibility complex class I gene is hormonally regulated. Further studies have shown increased activity of NF-kB in thyroid autoimmune diseases and in thyroid orbitopathy. Increased activity of NF-kB has also been observed in thyroid cancer, where it correlates with a more aggressive pattern. Of particular interest, mutation of some oncogenes or tumor suppressor genes involved in thyroid carcinogenesis results in constitutive activation of the NF-kB pathway. More recently, it has been shown that NF-kB also has a role in thyroid physiology, as it is fundamental for expression of the main thyroid-specific genes, such as sodium iodide symporter, thyroid peroxidase, thyroglobulin, Pax8, and TTF-1 (NKX2-1).